A method for preparing a low-pressure defect-free composite reverse osmosis membrane

By using the smooth surface filter membrane prepared by using the Free-Standing method as a support body, the interface aggregation reaction is performed to solve the problem of preparing high-efficiency reverse osmosis membrane under the concentration of low water phase, and achieve efficient chloride Sodium cutting and water molecular penetration reduced preparation costs.

CN116571093BActive Publication Date: 2025-01-28SHANDONG JINYU MEMBRANE TECH DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310295708.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-01-28
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

The prior art is difficult to prepare defect-free reverse osmosis membranes with a sodium chloride retention rate of >99.0% at low aqueous monomer concentrations, and the traditional interface polymerization method is affected by supporting pore size, surface roughness and other factors, resulting in polyamide separation layer. Roughness affects the transmembrane transportation of water molecules.

Method used

The filter membrane of ultra-thin thickness and smooth surface structures prepared by FREE-Standing method as a support body, by uniformly distributed the phenylramine between the water phase on the surface of the support body, and the interface reaction of the interface area of ​​the oil and water interface is formed. Defective polyamide separation function layer.

Benefits of technology

Achieved a non -defective reverse osmosis membrane of sodium chloride under low -water phase concentration (0.1 %) to prepare sodium chloride in the preparation of sodium chloride, which improved the separation performance and penetration flux of the membrane, reducing the preparation of preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116571093B_ABST
    Figure CN116571093B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a low-pressure defect-free composite reverse osmosis membrane; the method mainly comprises the following steps: using a Free-standing method nanofiltration membrane as a support, sequentially soaking an aqueous phase solution of m-phenylenediamine monomer and an oil phase solution of trimesoyl chloride monomer, performing an interfacial polymerization reaction, and obtaining a low-pressure defect-free composite reverse osmosis membrane after heat treatment. The novelty of the present invention patent is that: using a Free-standing method nanofiltration membrane with a smooth surface as a support, the m-phenylenediamine monomer is evenly distributed on its surface, and diffuses into the organic phase at a uniform speed to form a defect-free polyamide separation functional layer. The present invention uses a low concentration of m-phenylenediamine aqueous phase monomer (concentration <0.1%) to save the cost of reverse osmosis membrane preparation. The sodium chloride rejection rate of the prepared composite reverse osmosis membrane is >99.0%, and the permeate flux is >2.5L / (m 2 hbar).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a low-pressure defect-free composite reverse osmosis membrane. The low-pressure reverse osmosis membrane refers to a membrane with an operating pressure lower than 1.0 MPa, and the defect-free reverse osmosis membrane has a sodium chloride retention rate greater than 99.0%, belonging to membrane separation technology in chemical engineering. Background Art

[0002] Reverse osmosis membrane is a precision membrane separation product that can effectively intercept all dissolved salts and organic matter with a molecular weight greater than 100 Daltons, while allowing water molecules to pass through. The reverse osmosis membrane separation process has the advantages of low energy consumption, no pollution, simple process, and easy operation. Its NaCl retention rate is greater than about 95%, and the water permeability is 2-3L / (m 2 hbar), has been widely used in drinking water desalination and purification, brackish water desalination, seawater desalination, high-purity water preparation, industrial wastewater reuse, chemical process material concentration and other fields. The operating pressure of the reverse osmosis membrane is closely related to the salt content in the water. Drinking water has a low salt content, and the operating pressure of household reverse osmosis membranes is 0.3-0.6MPa, with a desalination rate of about 90-95%. In industrial groundwater and brackish water desalination, the operating pressure of the reverse osmosis membrane is 0.7-1.5MPa, and the desalination rate is 95-98%. The salt content of seawater is high, and reverse osmosis seawater desalination uses high pressure and ultra-high pressure operation, the pressure can reach 5-8MPa, and the desalination rate is as high as 99%. High-throughput defect-free reverse osmosis membranes can reduce equipment costs and operating costs, improve water purification capabilities, and at the same time improve material dehydration and concentration capabilities.

[0003] The material constituting the separation functional layer of the reverse osmosis membrane is mainly aromatic polyamide, which is prepared by interfacial polymerization. The interfacial polymerization method uses active polyamines (such as m-phenylenediamine, p-phenylenediamine, etc.) as water phase monomers and polyacyl chlorides (such as trimesoyl chloride) as oil phase monomers. The porous support (usually an ultrafiltration membrane) is first immersed in an aqueous solution, and the surface and pores of the porous support contain aqueous monomers. Then, after the surface of the support is dried with an air knife, the porous support is immersed in an organic phase solution. The polyamine and polyacyl chloride react chemically in the oil-water interface region on the surface of the support to form a dense polyamide separation layer. Finally, a composite reverse osmosis membrane is obtained by heat treatment. This traditional interfacial polymerization method is usually affected by factors such as the pore size, surface roughness, hydrophilicity and hydrophobicity of the porous support (usually an ultrafiltration membrane), and the distribution of aqueous monomers in the carrier pores. Because of the uneven distribution of water-phase monomers on the surface of the support and in the pores, uneven monomer diffusion occurs during the interfacial polymerization reaction, and the formed polyamide separation functional layer has a large roughness, showing a "ridge" or "valley" structure. High-concentration m-phenylenediamine water-phase monomers (concentration>2.0%) are usually used to prepare dense polyamide separation functional layers to improve the desalination rate of reverse osmosis membranes. High concentrations of water-phase monomers cause the polyamide separation layer to have a high thickness, which is not conducive to the transmembrane transport of water molecules. Using traditional interfacial polymerization methods, it is difficult to obtain defect-free reverse osmosis membranes with a sodium chloride rejection rate of>99.0% at low m-phenylenediamine water-phase monomer concentrations (concentration<0.1%).

[0004] The pore size of nanofiltration membrane is larger than that of reverse osmosis membrane, generally in the range of 1.0-2.0nm. The separation mechanism of nanofiltration membrane is pore screening and electrostatic repulsion, which allows solvent molecules, certain low molecular weight solutes, or monovalent inorganic ions to pass through the nanofiltration membrane; while ions with larger molecular weight or high valence inorganic salts cannot pass through the nanofiltration membrane. Nanofiltration membranes are used to remove organic matter and color from surface water, remove the hardness of groundwater, partially remove soluble salts, concentrate fruit juice, and separate and concentrate substances in chemical processes. The preparation method of conventional nanofiltration membrane is similar to that of reverse osmosis membrane. It also uses ultrafiltration membrane porous support, sequentially soaks piperazine aqueous phase monomer solution and benzyl chloride oil phase monomer solution, and forms the separation functional layer of nanofiltration membrane through interfacial polymerization reaction. Selecting nanofiltration membrane as support to prepare reverse osmosis membrane can eliminate the influence of pores. However, the surface of conventional nanofiltration membrane is rough, which is still not conducive to the uniform diffusion of monomers. The composite reverse osmosis membrane prepared with this as a support (comparative example experiment of the present invention) has a sodium chloride rejection rate of only about 96.0%, which does not meet the requirements of defect-free reverse osmosis membrane.

[0005] Table 1 Performance of ultrathin nanofiltration membranes prepared by free-standing method

[0006]

[0007] *See J.Materi.Chem.A., 2020, 8, 23930–23938.

[0008] Recently, the Free-standing method has been applied to the preparation of nanofiltration membranes, and the separation functional layer of the obtained nanofiltration membrane is thinner and smoother. The Free-standing method is to directly spread the oil phase monomer solution on the surface of the aqueous phase monomer solution. An ultra-thin polyamide nanofiltration membrane is first formed in the oil-water interface area, and then the polyamide nanofiltration membrane is transferred to the support, and the Free-standing method nanofiltration membrane is prepared by heat treatment. Since the Free-standing method pre-forms the polyamide separation functional layer and then transfers it to the porous support, the influence of the support can be eliminated. The aqueous phase monomer diffuses relatively evenly to carry out interfacial polymerization reaction, and the reaction heat is also quickly dissipated. Therefore, the Free-standing method can prepare an ultra-thin structure nanofiltration membrane with a smooth surface with a surface roughness of less than 2nm and a thickness of less than 20nm. The retention rate of sodium sulfate can be greater than 99.0%, and the water permeation flux is greatly improved (J. Mater. Chem. A, 2020, 45, 23930-23938, Desalination, 2023, 547, 116232). Table 1 shows the performance of the free-standing nanofiltration membrane reported in the literature. Graphene quantum dots are added to the aqueous solution as nanomaterials to regulate the diffusion rate of the aqueous monomer piperazine, further reduce the thickness of the polyamide separation layer of the nanofiltration membrane, and increase the permeation flux (J. Mater. Chem. A, 2020, 45, 23930-23938).

[0009] The present invention proposes: using a free-standing nanofiltration membrane with a smooth surface structure as a support, eliminating the influence of the rough surface of the conventional support, uniform interfacial polymerization reaction, forming a defect-free polyamide separation functional layer, and greatly improving the separation performance of the composite reverse osmosis membrane. Even at a very low aqueous monomer concentration, the sodium chloride rejection rate can be >99.0%, and the permeation flux can be >2.5L / (m 2 hbar). Summary of the invention

[0010] The present invention aims to provide a low-pressure defect-free composite reverse osmosis membrane and a preparation method thereof. The operating pressure of the reverse osmosis membrane is lower than 1.0 MPa, and the sodium chloride rejection rate is greater than 99.0%. The method uses a free-standing nanofiltration membrane with an ultra-thin thickness and a smooth surface structure as a support, and the aqueous phase monomer metaphenylenediamine is relatively evenly diffused, and an interfacial polymerization reaction is carried out at a uniform speed, so that a defect-free composite reverse osmosis membrane can be prepared at a low aqueous phase monomer concentration.

[0011] The technical solution of the present invention is as follows:

[0012] The invention discloses a method for preparing a low-pressure defect-free composite reverse osmosis membrane. The method comprises the following steps: using a free-standing nanofiltration membrane as a support, sequentially immersing the membrane in an aqueous solution containing m-phenylenediamine monomers and an oily solution containing trimesoyl chloride monomers, and performing an interfacial polymerization reaction; and obtaining the low-pressure defect-free composite reverse osmosis membrane after heat treatment. The mass fraction of the m-phenylenediamine in the aqueous phase is 0.01-0.1%; and the mass fraction of the trimesoyl chloride in the oily phase is 0.01-0.1%.

[0013] The free-standing method nanofiltration membrane is a support; the free-standing method nanofiltration membrane has an ultra-thin thickness and a smooth surface structure.

[0014] The graphene quantum dots or sodium dodecyl sulfate are selected as the water phase additive, and the concentration range is respectively 0-0.10% by mass fraction.

[0015] The trimesoyl chloride is an oil phase monomer, and the oil phase solution is preferably one or more combinations of n-hexane, n-heptane, and isoparaffin.

[0016] The nanofiltration membrane is preferably immersed in the aqueous solution for 0.5-15 min.

[0017] The nanofiltration membrane is preferably immersed in the oil phase solution for a reaction time of 0.5-5 min.

[0018] The composite reverse osmosis membrane is prepared by heat treatment, and the heat treatment temperature is preferably 50-90° C.; the heat treatment time is preferably 5-20 min.

[0019] The method of the present invention is used to prepare a low-pressure defect-free composite reverse osmosis membrane, which has high desalination performance, a sodium chloride rejection rate of >99.0%, and a permeation flux of >2.5L / (m 2 hbar).

[0020] The present invention proposes to prepare a low-pressure defect-free composite reverse osmosis membrane using a free-standing method nanofiltration membrane as a support. The nanofiltration membrane has an ultra-thin thickness (thickness <20nm) and a smooth surface structure (roughness <2nm) (see Table 1). Since the free-standing nanofiltration membrane has a small pore size, ultra-thin thickness and a smooth surface, the influence of the support on the diffusion of the aqueous phase monomer from the aqueous phase to the oil phase is reduced. The aqueous phase monomer m-phenylenediamine can diffuse relatively evenly into the oil phase, effectively reducing the influence of the uneven distribution of the monomer on the interfacial polymerization reaction, reducing the generation of interfacial defects in the polyamide separation functional layer, and obtaining a low-pressure defect-free composite reverse osmosis membrane after heat treatment. The present invention can significantly reduce the concentration of the aqueous phase monomer m-phenylenediamine (concentration <0.1%), saving the preparation cost of the reverse osmosis membrane. The low-pressure defect-free composite reverse osmosis membrane prepared by the patent of the present invention has a sodium chloride rejection rate of >99.0% and a permeate flux of >2.5L / (m2hbar).

[0021] The novelties of the present invention are: (1) Method innovation: using the free-standing method nanofiltration membrane as the support, the aqueous phase monomer m-phenylenediamine is evenly distributed on the surface of the support, diffuses to the organic phase at a uniform rate, and forms a defect-free polyamide layer through interfacial polymerization. (2) Structural innovation: using the free-standing method nanofiltration membrane as the support, the prepared reverse osmosis membrane has an ultra-thin and smooth structure, which greatly improves the separation performance of the reverse osmosis membrane. (3) Cost saving: a defect-free reverse osmosis membrane can be prepared at a lower aqueous phase monomer m-phenylenediamine concentration, which greatly saves the preparation cost of the reverse osmosis membrane.

[0022] This patent uses a free-standing nanofiltration membrane as a support to prepare a composite reverse osmosis membrane, thereby improving the overall performance of the composite reverse osmosis membrane. The smooth surface of the free-standing nanofiltration membrane allows m-phenylenediamine to be evenly distributed on its surface and diffuse into the organic phase at a uniform rate to form a defect-free polyamide separation layer. A lower concentration of aqueous phase monomer m-phenylenediamine can reduce the thickness of the separation functional layer of the reverse osmosis membrane. Anionic surfactants such as sodium dodecyl sulfate and graphene quantum dots can also be used as aqueous phase additives to regulate interfacial tension and diffusion of aqueous phase monomers during interfacial polymerization. The low-pressure defect-free composite reverse osmosis membrane prepared by the present invention has good desalination performance, with a sodium chloride retention rate of >99.0% and a permeate flux of >2.5L / (m 2 hbar). BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides a method for preparing a composite reverse osmosis membrane according to a specific embodiment of the present invention. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. The described specific embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0025] The low-pressure defect-free composite reverse osmosis membrane and the preparation method thereof of the present invention comprise the following processes:

[0026] Step 1: Preparation of nanofiltration membrane by free-standing method. Spread the oil phase solution of trimesoyl chloride on the surface of piperazine aqueous solution, and form a polyamide membrane in the oil-water interface area. Transfer to a porous support, and heat treat to obtain a nanofiltration membrane by free-standing method. The nanofiltration membrane by free-standing method has an ultra-thin thickness and a smooth surface structure, which can promote the uniform diffusion of aqueous phase monomers to participate in the interfacial polymerization reaction.

[0027] Step 2: Preparation of monomer solution required for reverse osmosis membrane preparation. Aqueous phase solution: m-phenylenediamine is the aqueous phase monomer, with a concentration of 0.01-0.10%. Graphene quantum dots and sodium dodecyl sulfate can be selected as aqueous phase additives, with a concentration range of 0-0.10%. Preparation of oil phase solution: trimesoyl chloride is the oil phase monomer, with a concentration of 0.01-0.10%. N-hexane, n-heptane or isoparaffin is the oil phase solution.

[0028] Step 3, preparation of low-pressure defect-free composite reverse osmosis membrane: Free-stangding method nanofiltration membrane is used as a support, and the aqueous solution of m-phenylenediamine and the oil solution of trimesoyl chloride are soaked in turn to perform interfacial polymerization reaction to form a polyamide separation functional layer, and a low-pressure defect-free composite reverse osmosis membrane is obtained after heat treatment. Using the free-standing method nanofiltration membrane, a low-pressure defect-free reverse osmosis membrane can be obtained under low aqueous phase monomer concentration conditions, which greatly improves the separation performance of the reverse osmosis membrane.

[0029] The present invention uses a free-standing nanofiltration membrane with ultra-thin thickness and smooth surface structure as a support, which overcomes the rough surface structure of traditional ultrafiltration membranes and nanofiltration membrane supports. The water phase monomers diffuse relatively evenly to participate in the interfacial polymerization reaction, eliminating the interface defects caused by non-uniform polymerization reactions. The free-standing nanofiltration membrane has a smooth surface with a roughness of less than 2nm, which eliminates the influence of the microscopic spatial structure of the support and realizes the uniform diffusion of the water phase monomers. Under low water phase monomer concentration conditions (m-phenylenediamine concentration <0.1%), a relatively uniform interfacial reaction can be achieved, spontaneously eliminating the defects of the interfacial polymerization polyamide membrane, and obtaining a defect-free reverse osmosis membrane with a sodium chloride retention rate of >99.0%. The present invention overcomes the limitation that traditional interfacial polymerization must use high water phase monomer concentrations (m-phenylenediamine concentration >2.0%), which can save the cost of reverse osmosis membrane preparation to a large extent. The low-pressure defect-free composite reverse osmosis membrane prepared by the present invention has high desalination performance, the operating pressure is lower than 1.0MPa, the sodium chloride rejection rate is >99.0%, and the permeation flux is >2.5L / (m 2 hbar). Specific embodiment 1

[0031] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0032] Preparation of nanofiltration membrane by free-standing method. Prepare water phase, piperazine with mass fraction of 0.0125%, graphene quantum dots with mass fraction of 0.01%. Prepare n-heptane organic phase solution, benzyl chloride with mass fraction of 0.01%. Prepare composite nanofiltration membrane by free-standing method.

[0033] like Figure 1 The preparation method of the composite reverse osmosis membrane is shown. The free-standing nanofiltration membrane is used as a support and immersed in an aqueous solution of 0.01% m-phenylenediamine and 0.01% sodium dodecyl sulfate for 15 minutes. Then it is immersed in an n-heptane oil phase solution of 0.01% trimesoyl chloride to carry out an interfacial polymerization reaction for 3 minutes. Finally, it is heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0034] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 2.9 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 98.9%. Specific embodiment 2

[0036] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0037] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0038] like Figure 1 The preparation method of the composite reverse osmosis membrane is shown. The free-standing nanofiltration membrane is used as a support and immersed in an aqueous solution of 0.0125% m-phenylenediamine and 0.01% sodium dodecyl sulfate for 15 minutes. Then it is immersed in an n-hexane oil phase solution of 0.01% trimesoyl chloride to carry out an interfacial polymerization reaction for 3 minutes. Finally, it is heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0039] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.2 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.0%. Specific embodiment 3

[0041] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0042] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1, except that the mass fraction of the graphene quantum dots is 0.015%.

[0043] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.01% m-phenylenediamine and 0.01% sodium dodecyl sulfate for 15 minutes. Then, an interfacial polymerization reaction was carried out in an oil phase solution of 0.01% trimesoyl chloride in n-heptane for 3 minutes. Finally, a heat treatment was carried out in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane 3.

[0044] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 2.6 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.2%. Specific embodiment 4

[0046] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0047] The free-standing method for preparing the nanofiltration membrane is the same as in Example 3.

[0048] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.0125% m-phenylenediamine and 0.01% sodium dodecyl sulfate for 10 minutes. Then, it was immersed in an n-heptane oil solution of 0.01% trimesoyl chloride for interfacial polymerization reaction for 3 minutes. Finally, it was heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0049] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 2.5 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.4%. Specific embodiment 5

[0051] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0052] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0053] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.0125% m-phenylenediamine, 0.005% graphene quantum dots and 0.01% sodium dodecyl sulfate for 5 minutes. Then, it was immersed in an oil phase solution of 0.01% trimesoyl chloride in n-heptane for interfacial polymerization for 3 minutes. Finally, it was heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0054] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.6 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.1%. Specific embodiment 6

[0056] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0057] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0058] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.0125% m-phenylenediamine, 0.0075% graphene quantum dots and 0.01% sodium dodecyl sulfate for 5 minutes. Then, it was immersed in an oil phase solution of 0.01% trimesoyl chloride in n-hexane for interfacial polymerization reaction for 3 minutes. Finally, it was heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0059] The low-pressure defect-free composite reverse osmosis membrane of this embodiment has a flux of 3.0 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.2%. Specific embodiment 7

[0061] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0062] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0063] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.02% m-phenylenediamine, 0.005% graphene quantum dots and 0.01% sodium dodecyl sulfate for 10 minutes. Then, it was immersed in an oil phase solution of 0.01% trimesoyl chloride in n-hexane for interfacial polymerization reaction for 3 minutes. Finally, it was heat treated in an oven at 70°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0064] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.3 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.2%. Specific embodiment 8

[0066] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0067] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0068] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.05% m-phenylenediamine, 0.0075% graphene quantum dots and 0.01% sodium dodecyl sulfate for 10 minutes. Then, it was immersed in an n-heptane oil phase solution of 0.01% trimesoyl chloride for interfacial polymerization reaction for 3 minutes. Finally, it was heat treated in an oven at 80°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0069] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.0 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.2%. Specific embodiment 9

[0071] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0072] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0073] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.1% m-phenylenediamine, 0.005% graphene quantum dots and 0.01% sodium dodecyl sulfate for 5 minutes. Then, it was immersed in an n-heptane oil phase solution of 0.01% trimesoyl chloride for interfacial polymerization reaction for 5 minutes. Finally, it was heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0074] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 2.8 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.0%. Specific embodiment 10

[0076] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0077] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0078] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.0125% m-phenylenediamine, 0.0075% graphene quantum dots and 0.01% sodium dodecyl sulfate for 5 minutes. Then it was immersed in an oil phase solution of 0.1% trimesoyl chloride in n-hexane for interfacial polymerization reaction for 2 minutes. Finally, it was heat treated in an oven at 50°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0079] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.4 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.1%. Specific embodiment 11

[0081] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0082] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0083] The nanofiltration membrane of the free-standing method was used as a support and immersed in an aqueous solution of 0.1% m-phenylenediamine, 0.005% graphene quantum dots and 0.01% sodium dodecyl sulfate for 0.5 min. Then, it was immersed in an isoparaffin oil solution of 0.01% trimesoyl chloride for interfacial polymerization reaction for 5 min. Finally, it was heat treated in an oven at 60°C for 10 min to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0084] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.1 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.3%. Specific embodiment 12

[0086] Preparation of low-pressure defect-free composite reverse osmosis membrane:

[0087] The free-standing method for preparing the nanofiltration membrane is the same as in Example 1.

[0088] The nanofiltration membrane of this free-standing method was used as a support and immersed in an aqueous solution of 0.05% m-phenylenediamine, 0.005% graphene quantum dots and 0.01% sodium dodecyl sulfate for 2 minutes. Then, it was immersed in a mixed oil phase solution of 0.01% trimesoyl chloride in n-hexane and n-heptane for interfacial polymerization reaction, and the reaction time was 1 minute. Finally, it was heat treated in an oven at 60°C for 10 minutes to obtain a low-pressure defect-free composite reverse osmosis membrane.

[0089] The low-pressure defect-free composite reverse osmosis membrane of this embodiment is operated at an operating pressure of 0.6 MPa and has a flux of 3.5 L / (m 2 hbar), the rejection rate of sodium chloride (0.1% aqueous solution) was 99.0%.

[0090] Although the above embodiments describe the present invention in detail, the present invention is not limited to the above specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many modifications without departing from the purpose of the present invention, which are all within the protection of the present invention.

Claims

1. A method for preparing a low-pressure defect-free composite reverse osmosis membrane, characterized in that: A free-standing nanofiltration membrane is used as a support, and an aqueous solution of m-phenylenediamine monomer and an oil phase solution of trimesoyl chloride monomer are sequentially immersed to perform an interfacial polymerization reaction; a low-pressure defect-free composite reverse osmosis membrane is obtained after heat treatment; the aqueous phase concentration of the m-phenylenediamine monomer is 0.01-0.1%; the oil phase concentration of the trimesoyl chloride monomer is 0.01-0.1%; Graphene quantum dots or sodium dodecyl sulfate are selected as aqueous phase additives, and the mass fraction concentration range is 0-0.10%, excluding the 0 point; the nanofiltration membrane is immersed in the aqueous solution for 0.5-15min; the nanofiltration membrane is immersed in the oil phase solution for 0.5-5min; the low-pressure reverse osmosis membrane refers to an operating pressure lower than 1.0Mpa; the low-pressure defect-free composite reverse osmosis membrane has high separation performance, sodium chloride retention rate>99.0%, permeation flux>2.5L / (m 2 hbar); The free-standing method nanofiltration membrane is used as a support; the free-standing method nanofiltration membrane has an ultra-thin thickness of <20nm and a smooth surface structure with a roughness of <2nm.

2. The method for preparing a low-pressure defect-free composite reverse osmosis membrane according to claim 1, characterized in that: Trimesoyl chloride is an oil phase monomer, and the oil phase solution is one or more combinations of n-hexane, n-heptane and isoparaffin.

3. The method for preparing a low-pressure defect-free composite reverse osmosis membrane according to claim 1, characterized in that: Heat treatment temperature is 50-90 o C; heat treatment time is 5-20min.

Citation Information

Patent Citations

  • Preparation method of polyamide composite reverse osmosis membrane

    CN113181779A

  • High-flux reverse osmosis composite membrane and preparation method thereof

    CN115318109A